2017
DOI: 10.1111/jiec.12532
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impacts of Capital Formation

Abstract: Summary The investment in capital goods is a well‐known driver of economic activity, associated resource use, and environmental impact. In national accounting, gross fixed capital formation (GFCF) constitutes a substantial share of the total final demand of goods and services, both in terms of monetary turnover and embodied resources. In this article, we study the structure of GFCF and the environmental impacts associated with it on a global scale, and link it to measures of development. We find that the share… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 46 publications
1
64
0
Order By: Relevance
“…; Södersten et al. ) provide a cause for concern for future growth. Likewise, the International Resource Panel of the UNEP has recently shown that an increase in resource efficiency is key for meeting climate‐change targets in a cost‐effective manner (Ekins et al.…”
Section: Resultsmentioning
confidence: 99%
“…; Södersten et al. ) provide a cause for concern for future growth. Likewise, the International Resource Panel of the UNEP has recently shown that an increase in resource efficiency is key for meeting climate‐change targets in a cost‐effective manner (Ekins et al.…”
Section: Resultsmentioning
confidence: 99%
“…To compare the impacts of creating U K from a more aggregated CFC dataset, we adapt the approach developed in Södersten et al. () for many countries in an MRIO to the USEEIO, aided by communication with the lead author (Miller, Södersten, Berrill, & Hertwich, ). We prepare the comparison matrix UKLEMS for the year 2007 since the CFC data is not available for 2012.…”
Section: Methodsmentioning
confidence: 99%
“…We enable the distribution of environmental impact of capital formation based on the depreciation of that capital in a given year, rather than the investment in that year, following Södersten et al. (). To demonstrate the advantage of using more detailed depreciation data, we compare outcomes using CFC data from BEA with the more aggregated KLEMS matrices.…”
Section: Objectivementioning
confidence: 99%
See 2 more Smart Citations